The Effect of Training Through Work Creativity on the Superior Performance of MSMEs (Msme's Excellent Performance) Fostered by the Integrated Business Service Center (PLUT) of the and MSMEs Cooperative Office of South Sulawesi Province" - Aly Anwar; Mattalata Mattalata; Ansar Ansar; Kurniawaty Kurniawaty (Journal of Social Science, 2024)
Micro, small and medium enterprises (MSMEs) have a strategic role in national economic development, in addition to playing a role in economic growth and labor absorption. The goal to be achieved in this study is to find out and analyze the superior performance of MSMEs (MSME Excellent Performance) by implementing Training through Work Creativity. This research is a quantitative research that examines scientifically and systematically the parts, phenomena and relationships between variables. The results of this study have significant implications for human resource development strategies and improving organizational performance, especially in the context of small and medium enterprises (MSMEs/SMEs). The findings show that training plays an important role in increasing work creativity (WCR), which directly affects the superior performance of MSMEs (SEPs). Referring to the formulation of the problem, the conclusion of this study is: training, which is good, has a significant influence in increasing Work Creativity significantly, but does not significantly contribute to improving the Superior Performance of MSMEs/SMEs's EXcellent Performance directly. Thus, this study proves that good Work Creativity is proven to be a good mediator and is able to increase the influence of training, coaching, and mentoring on the Superior Performance of MSMEs / SME's EXcellent Performance.